Robots and empire - Asimov, Isaac, 1920-; HarperVoyager (London : HarperVoyager, 1996)
Dr. Kelden Amadiro is determined to bring total annihilation of the planet Earth, but Lady Gladia vows to stop him at any cost and seal Earth's fate and all who live there.
Sequel to: The robots of dawn.
Young Adult.
Young Adult
Keywords: Baley, Elijah (Fictitious character) -- Fiction; Robots -- Fiction; Baley, Elijah (Fictional character) -- Fiction; Mystery fiction; Robots -- Fiction; Science fiction; Detective and mystery stories; Science fiction